Roll over, Tchaikovsky! : Russian popular music and post-Soviet homosexuality - Amico, Stephen (New perspectives on gender in music., 2014)
Centered on the musical experiences of homosexual men in St. Petersburg and Moscow, this ground-breaking study examines how post-Soviet popular music both informs and plays off of a corporeal understanding of Russian male homosexuality. Drawing upon ethnography, musical analysis, and phenomenological theory, Stephen Amico argues that the homosexual body in post-Soviet Russia rejects both the Soviet aversion to physical pleasure and the Western politicization of sexuality. Instead, both listeners and performers turn to popular music for a framework within which they can experience an embodied sense of sexuality, the self, and intersubjectivity.